MINIATURIZED AND CIRCULAR POLARIZED METAMATERIAL-INSPIRED ANTENNA FOR WIRELESS COMMUNICATION (REVUE ROUMAINE DES SCIENCES TECHNIQUES — SÉRIE ÉLECTROTECHNIQUE ET ÉNERGÉTIQUE, 2025)
In this paper, a miniaturized triple-band antenna is designed for wireless communication applications. The two inverted C-shaped strips are used to enhance the electric length, which improves the impedance bandwidth. The unit cell analysis of the inverted C-shaped strips indicates that the three bands are directly responsible for the negative permeability. The triangular-shaped parasitic stub is used in the ground to perturb the surface waves, which affects the CP behavior of the antenna at higher operating bands. The antenna bandwidths are obtained as follows: 2.37 GHz (2.337–2.405 GHz), 3.34 GHz (3.06–3.84 GHz), and 5.21 GHz (5.08–5.38 GHz), where the axial ratio is attained from 5 GHz to 5.35 GHz. The miniaturized size and triple-band antenna are well-suited for portable applications that require a compact design.
Keywords: Circular polarized antenna; triple-band antenna; Metamaterial Inspired antenna; 5G applications; WLAN applications